Cyber-diplomacy: cyberwarfare and the rules of engagement. Issue 4 (1st October 2020) - Lancelot, Jonathan F.
ABSTRACT: This article is designed to outline the lack of international rules of engagement in cyberspace, and how traditional practices and laws of war are applicable to cyberwarfare and how it is not. If there are any legal implications for cyberwarfare, there are very few. Any reasonable anticipation of reprisal after an initial cyberattack by a nation-state upon another is minimum. The problem of attributing a cyberattack to a source remains an enormous challenge for cyber-diplomacy, leading to critics who do not see cyberwarfare as a standalone danger to national security. Regardless of the critics, the Department of Defense (DoD) has established cyber operations as weaponized entities in its Law of War Manual, and there are historical examples that prove cyberwarfare can act as a dangerous weapon against critical infrastructure and exposed populations. If there continues to be a deficiency of understanding on the part of essential decisionmakers regarding the nature of cyberspace in policy, and a sustained escalation of nation-state on nation-state cyberattacks, without proper rules of engagement in this space with universal axioms of proportionality, the international community could end up in error with an unwanted conventional or nuclear war.